1,4-Bis{3-[4-(dimethylamino)benzylideneamino]propyl}piperazine - Xu, Rui-Bo (International Union of Crystallography, 2009)
The molecule of the title compound, C(28)H(42)N(6), has site symmetry [Image: see text] with the centroid of the piperazine ring located on an inversion center. The piperazine ring adopts a chair conformation. The benzene ring and propylpiperazine are on opposite sides of the C=N bond, showing an E configuration.